Dominance of Right Ovary Structures in Lactating Dairy Cows - J. S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 2018)
The objectives were to determine the absolute and relative ovary location of dominant and preovulatory follicles and corpora lutea (CL) present in ovaries before and during hormone synchronization and their associations with CL regression, ovulation, and pregnancy rates in lactating dairy cows. Cows were exposed to presynchronization treatments of PGF2a, GnRH, or both, 3 to 4 weeks before initiating a timed artificial insemination (AI) program (GnRH-1 – 7 days – PGF2α[1 dose or 2 doses 24 hours apart] – 56 hours after first or only dose of PGF2α– GnRH-2 – 16 hours – timed AI) in which cows were first inseminated at 72 ± 3 days in milk. Blood samples were collected to assess progesterone concentration before ovarian structures were mapped in 691 cows and before each hormone treatment (GnRH-1, PGF2α, and GnRH-2). Follicles that ovulated and CL were detected more often in right than left ovaries. Location of dominant follicles before GnRH-1 tended to be more right than left with co-dominant follicles in both ovaries. In response to GnRH, more left-ovary follicles ovulated contralateral to CL than right-ovary follicles, but fewer left-ovary follicles ovulated ipsilateral to CL (left to left and right to right). Dominance of right-ovary CL was less than 50% because of multiple CL in both ovaries before GnRH-1 (15.8%) and before PGF2α(35.6%), resulting from GnRH-1-induced ovulations in the latter case. Preovulatory follicles before PGF2αwere detected more often ipsilateral than contralateral to CL induced by GnRH-1, but were of equal frequency ipsilateral or contralateral to older CL present before GnRH-1. Death of the CL in response to PGF2αwas greater for cows bearing older CL (95.3%) or older CL + younger CL (93.7%) compared with cows bearing only younger GnRH- 1-induced CL (80.6%). Risk of CL death did not differ regardless of the ipsilateral or contralateral location of younger CL relative to older CL. Pregnancy rate was greater in cows having both older and younger CL (i.e., these cows had a CL at GnRH-1 and ovulated in response to GnRH-1) compared with cows having only a younger CL at PGF2α. Pregnancy rate also was greater for cows with younger CL when contralateral to older CL compared with cows bearing only younger or older CL before PGF2α. Percentage of female calves born resulting from eggs produced by left or right ovaries did not differ. In contrast, a tendency (P= 0.14) existed for more heifers to be born resulting from eggs produced by right than left ovaries for cows that conceived at first service than for cows that conceived at repeat AI services.
Keywords: ovary dominance; hormonal synchronization; CL death; fertility